Monensin suppresses EMT-driven cancer cell motility by inducing Golgi pH–dependent exocytosis of GOLIM4 - Xiaochao Tan; Derrick L. Cardin; Shike Wang; Yuting Xu; William K. Russell (Proceedings of the National Academy of Sciences, 2025)
Despite extensive efforts to develop strategies to inhibit cancer metastasis—the leading cause of cancer-related deaths—progress has been limited in recent decades. Epithelial-to-mesenchymal transition (EMT) initiates metastasis by enhancing the migratory capacity and plasticity of cancer cells, enabling them to escape the primary tumor site. Identifying vulnerabilities unique to mesenchymal cancer cells is, therefore, critical for developing effective antimetastatic therapies. Our prior research has highlighted the crucial role of the Golgi apparatus in EMT-driven cancer cell motility and metastasis. In this study, we investigated the antimigratory effects of various Golgi-disrupting compounds and identified Monensin, a polyether ionophore antibiotic, as a potent migration suppressor in mesenchymal non–small cell lung cancer (NSCLC) cells. Monensin treatment increases the pH within the Golgi lumen, inducing rapid exocytosis of the promigratory Golgi scaffold protein Golgi Integral Membrane Protein 4 (GOLIM4). GOLIM4 plays a key role in regulating cell motility and adhesion by modulating the post-Golgi trafficking of Talin 1 (TLN1), an essential focal adhesion component. Furthermore, we found that both GOLIM4 and TLN1 are highly expressed in mesenchymal cancer cells and are direct targets of microRNA-200b, a microRNA that is suppressed during EMT. Treatment with Monensin or depletion of GOLIM4 or TLN1 significantly impaired the migratory activity of mesenchymal NSCLC cells. In summary, this study demonstrates that Monensin exhibits potential antimetastatic activity by disrupting the promigratory GOLIM4–TLN1 axis in mesenchymal NSCLC cells.